2008
DOI: 10.1002/ijc.23708
|View full text |Cite
|
Sign up to set email alerts
|

The eukaryotic translation elongation factor eEF1A2 induces neoplastic properties and mediates tumorigenic effects of ZNF217 in precursor cells of human ovarian carcinomas

Abstract: Ovarian epithelial carcinomas (OECs) frequently exhibit amplifications at the 20q13 locus which is the site of several oncogenes, including the eukaryotic elongation factor EEF1A2 and the transcription factor ZNF217. We reported previously that overexpressed ZNF217 induces neoplastic characteristics in precursor cells of OEC. Unexpectedly, ZNF217, which is a transcriptional repressor, enhanced expression of eEF1A2. In our study, array comparative genomic hybridization, single nucleotide polymorphism and Affyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 25 publications
0
24
1
Order By: Relevance
“…The data presented here indicate that EEF1A2 is aberrantly expressed at high levels in some plasma cell neoplasms of mice and humans. This is the first example of EEF1A2 being expressed in a mouse tumor, although high-level expression has been documented in a variety of human tumors belonging to different cell lineages [1], [2], [3], [4], [5], [6], [7]. In contrast to earlier studies suggesting that increased expression of EEF1A2 is associated with terminal differentiation [35], normal mouse and human plasma cells were found to be EEF1A2-negative.…”
Section: Discussioncontrasting
confidence: 83%
“…The data presented here indicate that EEF1A2 is aberrantly expressed at high levels in some plasma cell neoplasms of mice and humans. This is the first example of EEF1A2 being expressed in a mouse tumor, although high-level expression has been documented in a variety of human tumors belonging to different cell lineages [1], [2], [3], [4], [5], [6], [7]. In contrast to earlier studies suggesting that increased expression of EEF1A2 is associated with terminal differentiation [35], normal mouse and human plasma cells were found to be EEF1A2-negative.…”
Section: Discussioncontrasting
confidence: 83%
“…Among the several candidates represented within the clones, the EEF1A2 and PTK6 genes, both at 20q13.3 and potential oncogenes, were more frequently gained in malignant pheochromocytomas. Up-regulation and amplification of EEF1A2 have been reported in various cancers, and also correlation to invasion has been observed (Zhu et al 2007, Sun et al 2008, Cao et al 2009). PTK6 has been proposed to promote cell migration and invasion in breast cancer, and aberrant high expression was reported in breast tumours and ovarian cancer (Schmandt et al 2006.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found that high levels of ZNF217 expression have been associated with resistance to chemotherapy and with deregulated apoptotic signals in breast cancer cells (10,11). The precise molecular mechanisms involved in ZNF217 prosurvival functions are currently unknown, but activation of the Akt pathway (10), ErbB3 overexpression (12), Aurora-A overexpression (11), deregulated expression of several members of the Bcl-2 family (11), eEF1A2 overexpression (13), and interaction with the HIF pathway (14) have been proposed.…”
Section: Introductionmentioning
confidence: 99%